Ethnobotanical studies of medicinal plants in Borneo: Bridging tradition and pharmaceutical research - Mukti, Bayu Hari (Health Sciences International Journal, 2024)
Borneo's rich biodiversity and long-standing traditions of plant-based healing offer a unique convergence of ethnobotany and pharmaceutical research. This review explores the medicinal plants used by indigenous communities in Borneo, emphasizing their role in traditional medicine and their potential for modern pharmaceutical applications. By documenting indigenous knowledge, we highlight key species with proven bioactive properties and examine the growing scientific evidence supporting their efficacy in treating conditions such as inflammation, infection, and chronic diseases. Moreover, we address the challenges of integrating indigenous knowledge with modern scientific research, particularly regarding intellectual property rights, sustainability, and the ethical implications of benefit-sharing. Emerging technologies such as metabolomics, genomics, and artificial intelligence are revolutionizing the field of ethnopharmacology, enabling more efficient identification of bioactive compounds and promoting sustainable harvesting practices. This review calls for increased interdisciplinary collaboration to bridge the gap between traditional medicine and pharmaceutical innovation, as well as the urgent need for conservation efforts to protect Borneo’s biodiversity and indigenous knowledge systems. Ultimately, the future of ethnopharmaceutical research in Borneo represents not only an opportunity for drug discovery but also a critical pathway for preserving cultural heritage and advancing sustainable development.